Role of Chemokines in the Development and Progression of Alzheimer’s Disease - Wojcieszak, Jakub; Kuczyńska, Katarzyna; Zawilska, Jolanta B. (Journal of molecular neuroscience, 2022)
Alzheimer’s disease (AD) is a progressive neurogenerative disorder manifested by gradual memory loss and cognitive decline due to profound damage of cholinergic neurons. The neuropathological hallmarks of AD are intracellular deposits of neurofibrillary tangles (NFTs) and extracellular aggregates of amyloid β (Aβ). Mounting evidence indicates that intensified neuroinflammatory processes play a pivotal role in the pathogenesis of AD. Chemokines serve as signaling molecules in immune cells but also in nerve cells. Under normal conditions, neuroinflammation plays a neuroprotective role against various harmful factors. However, overexpression of chemokines initiates disruption of the integrity of the blood–brain barrier, facilitating immune cells infiltration into the brain. Then activated adjacent glial cells–astrocytes and microglia, release massive amounts of chemokines. Prolonged inflammation loses its protective role and drives an increase in Aβ production and aggregation, impairment of its clearance, or enhancement of tau hyperphosphorylation, contributing to neuronal loss and exacerbation of AD. Moreover, chemokines can be further released in response to growing deposits of toxic forms of Aβ. On the other hand, chemokines seem to exert multidimensional effects on brain functioning, including regulation of neurogenesis and synaptic plasticity in regions responsible for memory and cognitive abilities. Therefore, underexpression or complete genetic ablation of some chemokines can worsen the course of AD. This review covers the current state of knowledge on the role of particular chemokines and their receptors in the development and progression of AD. Special emphasis is given to their impact on forming Aβ and NFTs in humans and in transgenic murine models of AD.